2011
DOI: 10.1103/physrevb.83.144518
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for spin mixing in holmium thin film and crystal samples

Abstract: In a number of recent experiments, holmium has been shown to promote spin triplet pairing when in proximity to a spin singlet superconductor. The condition for the support of spin triplet pairing is that the ferromagnet should have an inhomogeneous magnetic state at the interface with the superconductor. Here we use Andreev reflection spectroscopy to study the properties of single ferromagnet/superconductor interfaces formed of holmium and niobium, as a function of the contact resistance of the junction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This means that it is practically impossible to probe the effect that DWs have on the supercurrents that pass through them. As an alternative, intrinsically DW-like ferromagnets such as Ho can be used 36 and indeed our group 20 37 (see also Ref. 38 ) and Sosnin et al 19 have demonstrated results consistent with a triplet proximity effect in Ho-based junctions.…”
mentioning
confidence: 75%
“…This means that it is practically impossible to probe the effect that DWs have on the supercurrents that pass through them. As an alternative, intrinsically DW-like ferromagnets such as Ho can be used 36 and indeed our group 20 37 (see also Ref. 38 ) and Sosnin et al 19 have demonstrated results consistent with a triplet proximity effect in Ho-based junctions.…”
mentioning
confidence: 75%
“…The spatial oscillatory behavior of the superconducting condensate induced in the ferromagnet leads to interesting effects as oscillations of the density-of-state in F/S [3][4][5] and F/S/F [6] structures, oscillations of the Josephson current in S/F/S Josephson junction [7][8][9][10], and oscillations of the critical temperature [1]. Moreover, in the case of multi-domain ferromagnets or artificial multilayer structures with inhomogeneous magnetization, the singlet Cooper pairs from a superconductor can be transform into long-range triplet pairs that may explain the long-range Josephson coupling observed in S/F/S structures [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Triplet correlations also leads to a dependence of the critical current on the magnetic configuration of diverse S/F structures [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally [24][25][26] and theoretically [27][28][29][30] proved that Ho can convert the singlet state into spin-aligned triplet state. This conversion can open a proximity channel for singlet Cooper pairs into linear ferromagnets, resulting in T c reduction.…”
mentioning
confidence: 99%